Development of spotted wing drosophila in fruits of two raspberry cultivars : Razvoj octene mušice ploda u plodovima dvije sorte maline - Pajač Živković, Ivana (Array, 2020)
Spotted wing drosophila (Drosophila suzukii (Matsumura, 1931)) a polyphagous alien invasive species causes economic damages in cultivation of soft fruits all over the word. It is widespread in Croatia and considering that the economic damage occurred in greenhouse cultivation of soft fruit several years ago, new damage in this production can be expected. The pest development was monitored on 50 overripe fruits of cultivars 'Amira' and 'Sugana' cultivated in greenhouses in Zagreb in 2018 to investigate pest preference for these cultivars and to make a risk assessment in raspberry cultivation. Pest presence was recorded on both cultivars at the same time, and D. suzukii was dominant drosophilid species in development. Significantly more drosophilids as well as individuals of D. suzukii were developed on cultivar 'Amira'. On 'Amira' 373 female and 211 male of D. suzukii developed, while on 'Sugana' 253 female and 142 males developed. Average number of pests per fruit on 'Amira' counted 11.68 and on 'Sugana' 7.9. Drosophila suzukii develops in high populations in the greenhouse production of raspberry cultivars, which poses a serious risk for their cultivation in the study site.